Chicken soup for the soul : teens talk relationships : stories about family, friends, and love - Canfield, Jack, 1944-; Hansen, Mark Victor; Newmark, Amy. (Cos Cob, CT : Chicken Soup for the Soul Pub. LLC, 2008)
A compilation of true stories written by teenagers, and by adults writing about their teenage years, focusing on teen relationships with parents, friends, crushes, boyfriends and girlfriends.
Head over heals -- The importance of family -- The first kiss -- Friendships that go the distance -- Betrayal ... or not -- Oh brother, Oh sister -- The dreaded "Let's be friends" -- Breakups and healing -- Differences bring us closer -- Putting yourself out there -- Growing apart -- Through thick and thin -- In love.
"Our 101 best stories."
105537
Keywords: Teenagers -- Literary collections; Teenagers' writings; Teenagers -- Conduct of life -- Anecdotes; Teenagers -- Family relationships -- Anecdotes; Dating (Social customs) -- Anecdotes